Dye Contaminant Removal: Adsorption on Thermoplastic Starch/Kraft Lignin Composites and Photodegradation - de Freitas, Amanda S.M.; Rodrigues, Jéssica S. [UNESP]; Amaro, Stefanny F.; Ramos, Beatriz M.; Ferreira, Marystela (Sociedade Brasileira de Quimica (SBQ), 2025)
This study investigated the removal of contaminants in water by adsorption on thermoplastic starch (TPS) and kraft lignin (KL) composites. A study on the desorption of methylene blue (MB) and methyl orange (MO) dyes in water was also carried out, followed by the photodegradation of solutions containing dissolved dyes. Initially, the surface morphology of the TPS and TPS-KL films was analyzed by scanning electron microscopy, revealing advantageous characteristics for efficient adsorption of contaminants. Fourier transform infrared spectroscopy (FTIR) analysis made it possible to characterize the TPS and TPS-KL composites. The results demonstrate the reversibility of the process and confirm the lack of permanent chemical modification in the polymer matrix, indicating that the adsorption/desorption process is physical rather than chemical. This suggests that the adsorbent material can be reused without losing its fundamental structural properties. Furthermore, the study allows for verification of the chemical changes on the surfaces of the materials involved. Ultraviolet-visible spectroscopy (UV-Vis) results show that for MO, both substrates exhibited low adsorption capacity, with efficiency values close to 20%. In contrast, for MB, both composite materials displayed excellent dye adsorption rates, achieving efficiencies of 78% or higher. The photodegradation of adsorbed dyes revealed promising results.
Keywords: adsorption; desorption; dyes; photodegradation; water remediation